Evidence of Hiring Discrimination Against the Second Generation: Results from a Correspondence Test in the Swiss Labour Market - Zschirnt, Eva (Journal of international migration and integration, 2020)
While there is ample evidence of discrimination against ethnic minority candidates in hiring, most existing studies have focused on stigmatised immigrant groups. Using a correspondence test to ethnic discrimination in the Swiss labour market is enumerated, varying the a priori stigma of the immigrant groups. The field experiment compares candidates with Swiss names against candidates with German, Kosovar and Turkish names in a paired correspondence test spanning four occupations. Results from attitude research in Switzerland lead to the expectation that these groups will face different rates of discrimination, with candidates with Kosovar names being the most stigmatised and candidates with German names facing the least discrimination. Between October 2017 and April 2018, applications were sent in response to 560 real vacancies in the German-speaking area of Switzerland. Across the minority groups, the relative call back rate was 1.13, meaning that minority candidates have to write 1.13 times as many applications as majority candidates to be invited for a job interview. The relative call back rates differ by the ethnic origin: Germans experience almost no discrimination across all occupations, Turks face a relative call back rate of 1.14, and Kosovars encounter the highest relative call back rate across occupations (1.26). We conclude that existing studies may give the false impression that all immigrants suffer from substantive discrimination in the labour market because they focus on stigmatised groups.